Epidemiology of tuberculosis among children and adolescents in the USA, 2007-17: an analysis of national surveillance data - Tori L Cowger, MPH; Jonathan M Wortham, MD; Deron C Burton, MD (Elsevier, 2019)
Summary: Background: Understanding tuberculosis epidemiology among children and adolescents informs treatment and prevention efforts, and efforts to eliminate disparities in tuberculosis incidence and mortality. We sought to describe the epidemiology of children and adolescents with tuberculosis disease in the USA, including tuberculosis incidence rates by parental country of birth and for US territories and freely associated states, which have not been previously described. Methods: We analysed data for children aged younger than 15 years and adolescents aged 15-17 years with tuberculosis disease reported to the National Tuberculosis Surveillance System during 2007-17, and calculated tuberculosis incidence rates using population estimates from the US Census Bureau. Findings: During 2010-17, 6072 tuberculosis cases occurred among children and adolescents; of these, 5175 (85%) of 6072 occurred in the 50 US states or the District of Columbia and 897 (15%) of 6072 in US-affiliated islands. In US states, 3520 (68%) of 5175 cases occurred among US-born people overall, including 2977 (76%) of 3896 children and 543 (42%) of 1279 adolescents. The incidence rate among children and adolescents was 1·0 per 100 000 person-years during 2007-17 and declined 47·8% (95% CI −51·4 to −44·1) during this period. We observed disproportionately high tuberculosis rates among children and adolescents of all non-white racial or ethnic groups, people living in US-affiliated islands, and children born in or with parents from tuberculosis-endemic countries. Interpretation: Overall, tuberculosis incidence among children and adolescents in the USA is low and steadily declining, but additional efforts are needed to eliminate disparities in incidence and mortality. Funding: US Centers for Disease Control and Prevention.